(untitled) (Revista científica Olimpia, 2020)
The objective of this study consisted in determining the existent limitations in the program of physical recreation as from the contents of physical recreational activities like educational form toward the community according to exchange currents provoked in indications and according to intentional, systematic character and guided in that connection. The methodology consisted in an analysis of the mode of acting of the professor to plan the activities according to the integrative project of sports combinations in practice. The analysis demonstrated insufficiencies in the selection of the contents like tool dinamizer within the communal context to conform a recreational and educational culture in one’s free time. That had influence upon the improvement of the variable investigated in the 95 % of sign and it evaluated me of very made suitable. One came to an end based in that pre-experiment: Lack of preparation of the professor has an effect on the determination of the contents of physical recreation to generate alternatives of educational form toward a correct constructive utilization of the free time of the community.